KATA KERJA BANTU DALAM ALBUM OVEREXPOSED DAN V OLEH MAROON 5 - KOTULUS, VEILLY CHRISTOVER (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT In English, there are two subclasses of verb, they are lexical verbs and auxiliary verbs. Auxiliary verb is a helping verb which grammatically functions to form or to add meaning of the verb phrase. This study is an attempt to describe and analyze the auxiliary verbs which are found in the Album of Maroon 5 Overexposed and V. The aim of this research is to classify and identify the form, meaning and function of auxiliary verb used in the film. The method used in this research is descriptive method. The data of auxiliary verbs have been taken from the sentences in the album of Maroon 5 Overexposed and V and analyzed by using Hudson?s concept. The results of this study show that the auxiliary verbs found in the two album of Maroon 5 are categorized into two classes: primary auxiliary verb (am, is, are, were, was) and modal auxiliary verbs (can, could, may, might, will, would, should) however must, shall, be to, used to, need, be supposed to and dare are not found in these album. In terms of the meaning, the primary auxiliary verbs have no meaning in themselves, but the modal it means auxiliary verbs have their own meaning depending on the context. Can means ability and with negative it means inability. Could means ability and with negative it means inability. May means possibility. Will means willingness, representation of some situation, promise and agreement. Would means willingness. Should means obligation. —————————————————————- Keywords: Auxiliary verb, Overexposed, V